Vps28 Is Involved in the Intracellular Trafficking of Awd, the Drosophila Homolog of NME1/2 - Mezzofanti, Elisa; Ignesti, Marilena; Hsu, Tien; Gargiulo, Giuseppe; Cavaliere, Valeria (Frontiers in Physiology, 2019)
The awd (abnormal wing discs) gene is the Drosophila homologue of human NME1 and NME2 metastasis suppressor genes. These genes play a key role in tumor progression. Extensive studies revealed that intracellular NME1/2 protein levels could be related to either favorable or poor prognosis depending on tissue context. More recently, extracellular activities of NME1/2 proteins have also been reported, including a tumor-promoting function. We used Drosophila as a genetic model to investigate the mechanism controlling intra- and extracellular levels of NME1/2. We examined the role of several components of the ESCRT (endosomal sorting complex required for transport) complex in controlling Awd trafficking. We show that the Vps28 component of the ESCRT-I complex is required for maintenance of normal intracellular level of Awd in larval adipocytes. We already showed that blocking of Shibire (Shi)/Dynamin function strongly lowers Awd intracellular level. To further investigate this downregulative effect, we analyzed the distribution of endosomal markers in wild type and Shi-defective adipocytes. Our results suggest that Awd trafficking does not involve CD63-positive endosomes. Interestingly, we found that in fat body cells, Awd partly colocalizes with the ESCRT accessory component ALiX, the ALG‐2 (apoptosis-linked gene 2)-interacting protein X. Moreover, we show that the intracellular levels of both proteins are downregulated by blocking the function of the Dynamin encoded by the shibire gene.